2020
DOI: 10.1055/s-0040-1708046
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Consequences of Postoperative Delirium in Cardiac Surgery

Abstract: Background Delirium is a common complication after cardiac surgery that leads to increased costs and worse outcomes. This retrospective study evaluated the potential risk factors and postoperative impact of delirium on cardiac surgery patients. Methods One thousand two hundred six patients who underwent open-heart surgery within a single year were included. Uni- and multivariate analyses of a variety of pre, intra-, and postoperative parameters were performed according to differences between the deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 31 publications
4
30
1
2
Order By: Relevance
“…The Melbourne Group Scale (MGS) ( 61 ) was used in this study to assess the occurrence of PPC in patients: Temperature>38°C, White cell count >11.2 or respiratory, antibiotics, Physician diagnosis of pneumonia or chest infection, Chest X-ray report of atelectasis/consolidation, Production of purulent (yellow/green), sputum differing from preoperative Positive signs on sputum microbiology, SpO 2 < 90% on room air and Re-admission to or prolonged stay (over 36 h) on the intensive care unit/high dependency unit for respiratory problems PPC = four or more positive variables. Studies have shown multiple correlations between pulmonary complications and POD, which are mutually causal ( 62 ). Patients with pulmonary complications after aortic dissection surgery are prone to hypoxemia, which causes cerebral hypoperfusion and leads to neuroinflammation, as a cause of POD ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Melbourne Group Scale (MGS) ( 61 ) was used in this study to assess the occurrence of PPC in patients: Temperature>38°C, White cell count >11.2 or respiratory, antibiotics, Physician diagnosis of pneumonia or chest infection, Chest X-ray report of atelectasis/consolidation, Production of purulent (yellow/green), sputum differing from preoperative Positive signs on sputum microbiology, SpO 2 < 90% on room air and Re-admission to or prolonged stay (over 36 h) on the intensive care unit/high dependency unit for respiratory problems PPC = four or more positive variables. Studies have shown multiple correlations between pulmonary complications and POD, which are mutually causal ( 62 ). Patients with pulmonary complications after aortic dissection surgery are prone to hypoxemia, which causes cerebral hypoperfusion and leads to neuroinflammation, as a cause of POD ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Delirium represented 42% of people in the case group, where CPB time had a relevant association with infectious complications. Similarly, longer aortic cross-clamp time was found to be a risk factor for postoperative delirium in one study [Sugimura 2020], and a longer duration of extracorporeal circulation was associated with the presence of delirium in others [Jones 2019;Sanson 2018].…”
Section: E744mentioning
confidence: 92%
“…We selected 21 perioperative demographic data or potential risk factors based on the previous studies and clinical experience ( 22 , 23 ). Two researchers independently collected the perioperative parameters based on medical record.…”
Section: Methodsmentioning
confidence: 99%